Vključevanje poklicnega profila šolska medicinska sestra v slovenske šole - Torkar, Tanja (Obzornik zdravstvene nege, 2013)
Introduction: In this article we discuss the rationale and possibilities to provide school health services in Slovenian schools as is the common practice in many schools abroad. School nursing ensures preventive services, early identification of problems, interventions, and referrals and advances the general well being of students during the school day. The aim of the study was to gather information about the teachers' and healthcare professionals' experiences and views about school nursing in Slovenia. Methods: A qualitative research, method was employed in the study. Semi-structured interviews were conducted (four focus groups and two individual interviews). The interviews were analyzed with the open coding method. Results: The analysis yielded five main categories: children's health problems at school, interventions conducted while children are at school, teachers' ability to recognize and act upon children's health issues, health promotion at school, and the need for health care professionals at schools. Discussion and conclusion: The teachers can not and should not assume the responsibility to intervene with diverse students' actual and potential health problems and therefore welcome the presence of a school nurse during the school day. The healthcare professionals participating in the study recognize and appreciate the significance of school nursing. They are, however, convinced that restructuring of health care organization in Slovenia and ensuing introduction of school nursing in the near future is hardly expected. Further research is needed to substantiate the need of school nursing within the health care system of Slovenia.
Keywords: health education; health problems; nursing; osnovna šola; primary school; students; učenci; zdravstvena nega; zdravstvena vzgoja; zdravstvene težave